Penguasaan pengetahuan konten: pencapaian pelajar sains sukan tingkatan enam di negeri Kedah / Saidil Mazlan Abdul Razak ... [et al.] - Abdul Razak, Saidil Mazlan; Elumalai, Gunathevan; Mohamad Hashim, Junaidy; Abdullah, Norliza (2018)
This study aims to identify a basic knowledge level of sport science contents among Form Six students. The study involves the Form Six Sports Science students in one of the schools in Kedah. The selection of the students to be enrolled in Sports Science course depending on the students'preference and there is no mechanism used by teachers in determining the selection. Therefore, this study aims to identify the level of basic knowledge acquired by the new Sport Science students who have chosen the course. The were 21 students (8 boys and 13 girls) regarded as the samples of this study. Samples were selected using a simple random sampling method. This study was conducted using the Sports Science Basic Knowledge Content instrument in the form of multiple answers choices. Validity value r = .93. This instrument covers four areas of sports science namely the Sports Science, Anatomy and Physiology Introduction, Physical Fitness and Sports Coaching. Each question was analyzed using the Difficulty Index and shows value of d = .60. Descriptive analysis showed that the Form Six Sports Science male students of 3 students or 32.5% were at good level. 5 students at a very good level representing 62.5%. Meanwhile, for girls, 1 person is at an very good level or 7.7%. The good level was represented by 7 students or 53.8% and a total of 5 students or 38.5% represented a moderate level. The findings of the study was using statistical analysis of t-test inference showed significant differences between men and women as a whole t (49) = 3.153, p = .003, p < 0.05 was significant. Test results showed that there is a significant difference in the level of achievement of the basic knowledge of the overall sport science content amongst male students (M = 45.33, SD = 7.51) with female students (M = 37.68, SD = 9.42). This finding is expected to help the students and teachers in ensuring the studentts to have a basic knowledge of sports science content before being given the option to enroll in the Form Six sports science course, therefore producing quality students.